Finding Fran: History and Memory in the Lives of Two Women by (Lois W. Banner. New York: Columbia University Press, 1998. 243 pages.) (American Journal of Islam and Society, 2001)
Finding Fran is a memoir of two women, once best friends, who take verydifferent paths. The author is now a feminist history professor and her highschool friend, Fran, is Noura-a Muslim living in Egypt Banner looksback on their lives to find out what led one to feminism and the other toIslam. Unfortunately, while Banner offers many interesting insights into thelives of both women, she never fully answers this fundamental question.The book is divided into four parts. Part I, "My Story (1944-1952),"explores Banner's family history as well as her life up Wltil high school. Shetraces the lives of various family members in order to discover how theyaffected her childhood and her outlook on life. In the second part, "Fran &Me (1952-1956)," Banner tells the story of their high school friendship.It is a friendship of two smart and artistically talented girls, who are oftenbold and passionate in a time and place that glorified passive, femininewomen. Together they navigate the seemingly esoteric system of footballplayers and prom queens without ever really belonging to that system.In college they separate, Banner to UCLA and Fran to Stanford. This isthe beginning of their two different paths. Banner takes to academia andfeminism, while Fran is drawn to the various spiritual movements of the1960s. These years are covered in the third section, "Passages (1956-1982)." Banner includes chapters on their college life and the yearsimmediately following, and then delves into her life as an academic and afeminist.The last section covers Fran/Noura's life between 1967 and 1990. Shestudies Zen and other spiritual movements, such as the Gurdjieff system. Inlate 1960s, she moves to a commune in New Mexico. There she discoverswesternized Sufi practices that have been cut from their Islamic base. Hercontinuing quest leads her to study Islam. She eventually becomes aMuslim and a member of a traditional Sufi order. Later, she studies in SaudiArabia, and currently, she residues in Egypt.In keeping with the personal nature of the book, Banner includes acollection of photographs ranging from old family snapshots to the twowomen together in high school in 1956 and again in Egypt in 1992. Muchof Banner's analysis comes in the prologue and the epilogue. She alsoincludes detailed notes for each chapter ...